Application of Three-Dimensional Electrical Resistivity Tomography in Archeological Prospection. Issue 1 (February 2021) - Liu, Chenyang; Yin, Zhaozhuo; Du, Lizhi
Abstract: As the important part of historical relics, ancient architectural sites contain an amount of cultural information, which are of great significance for the future development of mankind. But improper prospection methods will lead irreversible damage to the existing architectural sites. Therefore, appropriate detection methods have significant meaning in archeological prospection and cultural relic protection. At present, there are many methods to explore ancient architectural sites, among which three-dimensional electrical resistivity tomography (ERT) methods are gradually popularized, because of its advantages of non-destructive, high efficiency, economic and deep prospection. But there are too many electrode arrays, such as Wenner array, Schlumberger array, dipole-dipole array and pole-pole array. First, this paper briefly introduces the application status of ERT. Then, a simple geoelectric model is constructed, and the inversion results are obtained with different arrays. The comparison of the inversion results for 4 electrode arrays shows that the dipole-dipole array gives the highest resolution. And, a more complex geoelectric model is constructed and compared with the results of the inversion. The results show that conclusions have a good consistency. And, this paper shows that Wenner method and Schlumberger array have high resolution in archeological prospection.